The ever-changing ideal: The body you want depends on who else you're looking at. (March 2021) - Aniulis, Ellie; Sharp, Gemma; Thomas, Nicole A.
Highlights: This study examined the selection of ideal body size in adult women. Body ideals can change depending on the size of bodies women are exposed to. When exposed to more large body types, women idealise an underweight body less. Ideal body size perceptions change rapidly, immediately following exposure to available reference bodies. Abstract: The body positivity movement—celebrating bodies beyond the thin ideal—has gained traction on social media. In an online study of North American women, we aimed to determine how ideal body perceptions shift based on the presentation of more diverse body types. In Study 1, women ( n = 115, aged 19–75) responded to arrays of bodies ranging from primarily small to primarily large bodies, selecting the body closest to their ideal body. Results showed that the BMI of the ideal body increased as the body sizes in the array increased. Participants were also less likely to select an underweight ideal when viewing larger bodies. In Study 2, women responded to arrays with either primarily small ( n = 132, aged 20–68) or primarily large ( n = 130, aged 20–75) bodies. Results suggested that ideal body perceptions only shifted around current societal standards, and not to extremes. The participants presented with the larger-bodied arrays were more likely to select a normal weight ideal body than those who saw the smaller-bodied arrays. Results suggest ideal body size is malleable, and shifting toward a more diverse perception of the ideal body is achievable with increased exposure beyond the thin ideal.